2004
DOI: 10.1530/rep.1.00093
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of mitochondria in reconstructed mouse oocytes

Abstract: It has been suggested that nucleus replacement (transfer) may be used as an efficient oocyte therapy in order to prevent transmission of mutated mitochondrial DNA from mother to offspring in humans. The essential and not yet answered question is how mitochondria surrounding the karyoplast will be distributed in the newly reconstructed oocytes. In our model experiments, we have evaluated the distribution of mitochondria in reconstructed immature mouse oocytes when germinal vesicle karyoplasts, with labeled mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 30 publications
0
27
1
Order By: Relevance
“…This may be solved eventually by mitochondria-free karyoplasts. In the present study, oocyte centrifugation before manipulation led to the isolation of karyoplasts with a negligible amount of mitochondria (4.3%), lower than that approximated in previous reports (11,34), therefore preventing the heteroplasmy which would result from the mixture of karyoplast and cytoplast mitochondria, as recently suggested (21,47). However, given the potential for following a clinical approach of ooplasm donation and GVT in humans (48,49), efforts still need to be made to evaluate such treatments for both efficacy and safety in an appropriate animal model.…”
Section: Figurecontrasting
confidence: 47%
See 1 more Smart Citation
“…This may be solved eventually by mitochondria-free karyoplasts. In the present study, oocyte centrifugation before manipulation led to the isolation of karyoplasts with a negligible amount of mitochondria (4.3%), lower than that approximated in previous reports (11,34), therefore preventing the heteroplasmy which would result from the mixture of karyoplast and cytoplast mitochondria, as recently suggested (21,47). However, given the potential for following a clinical approach of ooplasm donation and GVT in humans (48,49), efforts still need to be made to evaluate such treatments for both efficacy and safety in an appropriate animal model.…”
Section: Figurecontrasting
confidence: 47%
“…GVT has been indicated as a possible treatment to correct age-related aneuploidy caused by dysfunctional ooplasm (15,20) and as a therapeutic advancement which could help prevent the transmission of mutated mitochondrial DNA from mother to offspring (21)(22)(23).…”
mentioning
confidence: 99%
“…However, in a few embryos, some donor mtDNA was detected at considerably increased levels, clearly indicating the occurrence of premature mtDNA replication. While this could result from the close proximity of the somatic mtDNA to the nucleus , this is likely to have occurred only prior to the first cleavage stage, as the donor mtDNA will have dispersed to varying regions of the cytoplasm in the newly formed blastomeres (Fulka 2004). Consequently, in these exceptional cases, it is more likely that the nuclear-encoded replication factors interacted with their own mtDNA more efficiently and hence replicated it preferentially, especially as POLG was expressed throughout early development for both mtDNA 1 and mtDNA R embryos (see Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…However, even in this case, it is necessary to know how the introduced mitochondria will be distributed in reconstructed cells [24,25]. It has been demonstrated that the speed of mitochondria distribution is cell-cycle dependent [14].…”
Section: Destruction Of Mutated Mitochondrial Dnamentioning
confidence: 99%